The Heritage of the Old Believers in Vilnius and its Role in Cultural Tourism - Ladyš, Violeta (Slavistica Vilnensis, 2018)
[full article, abstract in Lithuanian; abstract in Russian and English] The aim of this article is to present tangible heritage elements of the Old Believers’ culture in Vilnius, which is potentially important for representing the community of the Old believers in the Vilnius market of cultural tourism. As the sector of cultural tourism provides the preconditions for representation and maintanence of the cultural heritage and the memorial places of confessional minorities, the heritage of Vilnius Old Believers was chosen to be represented in the context of tourism market. The article consists of two main sections. The first section demonstrates the tangible immovable heritage of the Old Believers who had settled in Vilnius in the 1830s. The objects that immortalize the memory of the Old Believers were distinguished. The second section contains the review of travel guides in Vilnius of the second half of nineteenth to twentieth centuries and distinguishes the representation trends of the Old Believers, trends that depended on the government’s specific approach toward the Old Believers, their religijon and culture in general.